Gujarat Gram 5 A high yielding desi chickpea variety for North Hill Zone of India - Pithia, M S; Javia, R M; Ramani, V V; Andani, V P (Indian Farming, 2018)
Sixty front-line demonstrations on GG 5 were conducted in Gujarat during 2015-16 under irrigated condition. Breeder seed production programme of GG 5 has been conducted during 2015-16 and estimated 1200 kg breeder seed will be produced and made available to different agencies for large scale multiplication.